Body Mass Index, Age, and Gender on Bone Mineral Density in the Elderly - HALIMSETIONO, ELITA (JURNAL KESEHATAN PRIMER, 2025)
Introduction: Osteoporosis is a chronic bone disease caused by reduced bone mass and impaired bone structure. This disease is a widespread and serious public health problem. The most common consequences of this condition are hip and vertebral fractures, which can carry a substantial risk of premature morbidity and mortality. The best strategy to overcome osteoporosis is prevention by identifying risk factors and early diagnosis. This article aims to provide an overview of the influence of body mass index (BMI), age, and gender on bone mineral density (BMD) in the elderly. Methods: This article is a literature review with a search for literature sources using the keywords bone mineral density, body mass index, age, gender, and elderly in the Google Scholar, PubMed, PMC, Researchgate, and Sciencedirect databases. The inclusion criteria are online and full-text scientific articles in the last 10 years in international journals. Results: Several studies have shown that the prevalence of osteoporosis is higher in people with low BMI, but other studies have found a decrease in BMD in obese subjects; with increasing age there is a decrease in osteoblast differentiation and activity, increased osteoclastogenesis and osteoclast activity, and increased bone resorption; females are more susceptible to osteoporosis because decreased estradiol during menopause causes a sharp increase in bone turnover and resorption. Conclusion: There are mixed findings regarding the relationship between BMI and BMD. Age is a factor that needs to be considered because a person's chances of developing osteoporosis will increase with age. Females are more susceptible to osteoporosis.